PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA SEKTOR PROPERTY AND REAL ESTATE - Elsa Paulina Tjipto (Business Accounting Review, 2016)
The objective of this reseach was to find out whether or not Corporate Social Responsibility (CSR) had influence on the firm value, in which the CSR variable was measured based on the Gloal Reporting Initiative Index 3.1 standart, while firm value was measured by using Tobin’s Q. The sample was taken form the observation of 116 companies in Property and Real Estate sector within 2009-2013. The result of this reserch showed that Corporate Social Responsibility had significant influance on the firm value, while the other control variables, namely firm size, market share and debt to equity ratio had no influence on the firm value.